2021
DOI: 10.1007/s00432-021-03708-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy and safety of regorafenib plus drug-eluting beads-transarterial chemoembolization versus regorafenib monotherapy in colorectal cancer liver metastasis patients who fail standard treatment regimens

Abstract: Objective This study aimed to evaluate the efficacy and safety of regorafenib plus drug-eluting beads-transarterial chemoembolization (DEB-TACE) versus regorafenib monotherapy in colorectal cancer liver metastases (CRLM) patients who failed standard treatment regimens. Methods Totally, 76 eligible CRLM patients were analyzed, among which 42 patients received regorafenib monotherapy (as regorafenib group) and 34 patients received regorafenib plus DEB-TACE (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…A previous study reported that the ORR of regorafenib was 7.7% and the DCR was 53.4% (16). Another study also reported that the ORR of regorafenib combined with TACE was 35.3% and the DCR was 76.5% (17). In this study, as a second-line targeted drug, regorafenib had an ORR of 14.0-22.0% and a DCR of 62.0-60.0%.…”
Section: Discussionsupporting
confidence: 61%
“…A previous study reported that the ORR of regorafenib was 7.7% and the DCR was 53.4% (16). Another study also reported that the ORR of regorafenib combined with TACE was 35.3% and the DCR was 76.5% (17). In this study, as a second-line targeted drug, regorafenib had an ORR of 14.0-22.0% and a DCR of 62.0-60.0%.…”
Section: Discussionsupporting
confidence: 61%
“…Drug-eluting bead (DEB) embolization uses a new type of drug-loaded microspheres that can continuously kill tumors by slowly releasing drugs [ 6 , 7 ]. Studies have proved that DEB embolization shows a good treatment effect for metastatic liver cancer [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this study is a first of its kind in exploring the feasibility, prognosis, and toxicity of HAIC combined with regorafenib for the treatment of patients with predominant liver metastasis of CRC and failure to first/second-line treatment. In real-world clinical cases, diffuse, multiple, and a high percentage of liver involvement in CRLM with disease progression that fails at least 2–3 prior standard systemic therapies prove to be problematic posing a tremendous therapeutic challenge [ 39 ]. In this research, results from the given treatment showed promising DCR, median OS, and was well-tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cao et al showed that the regorafenib plus drug-eluting-beads-TACE group yielded a higher median PFS than the regorafenib-only group (7.6 vs. 4.1 months, P < 0.001, respectively) in CRLM that has not responded to the standard treatment regimens. The median OS was also higher in the regorafenib plus drug-eluting-beads-TACE group versus the regorafenib-only group (15.7 vs. 9.2 months, P < 0.001) [ 24 ]. Many studies have confirmed the efficacy of tyrosine kinase inhibitors (TKI) such as regorafenib and sorafenib combined with HAIC in the localized treatment strategies of TACE in hepatocellular carcinoma [ 25 28 ].…”
Section: Introductionmentioning
confidence: 99%